A Case of Transient Monocular Vision Loss and Paracentral Acute Middle Maculopathy. Issue 3 (September 2021) - Betsch, Devin M.; Mishra, Amit V.; Freund, Paul R.
Abstract : Abstract: A 77-year-old man with multiple cerebrovascular risk factors presented with a history of transient monocular vision loss and residual paracentral visual disturbance in the right eye. Carotid ultrasounds, erythrocyte sedimentation rate, and C-reactive protein were all within normal limits. He was found to have retinal whitening within the macula in the right eye, corresponding to an area of decreased retinal perfusion on optical coherence topography (OCT)-angiography and a hyperreflective middle retina band on spectral domain-OCT. This was consistent with a diagnosis of paracentral acute middle maculopathy (PAMM). PAMM should be considered a part of the differential diagnosis in patients with focal visual disturbances, and OCT studies are recommended as part of the work up as subtle fundus findings may be missed.